Наголос у структуруванні українського діалектного континууму (дисертація на здобуття наукового ступеня доктора філологічних наук зі спеціальності 10.02.01 – українська мова. Інститут української мови НАН України) - Кобиринка, Галина (Gwary Dziś, 2022)
The article views the accent in nouns, adjectives, numerals and pronouns in Ukrainian dialects from the perspective of accent types (fixed / lexical stress). Namely, to some extent the models, the principles of studying and describing the dialectal accent system correlate with the principles, methods of studying the accent system of the literary standard. At the same time, the latter have their own specifics, primarily awareness and researcher orientation in space and time. We need to take into account not only the codified norm but also an area of the dialectal system study, the history of its formation and the age-related characteristics of the speakers.Emphasis Has been placed on the fact that every part of speech has its traits in a grammatical structure, which involves the use of different methods of emphasis. The study analyzes fixed stress placed on the penultimate syllable of a word – a paroxiton, which is definitely opposed to lexical stress. The proposed identified determination of paroxitonic emphasis: fixed stress on the penultimate composition of a word, which may be a constant feature, and paroxitonosis against lexical stress. In the accentuational portraits of Ukrainian zones it was found out that accentuation is an important argument in determining the maternal basis of new-life, transitional and resettlement (island) dialects. The Southwest type of stress is proposed as a territorial literary-normative variant. It is emphasized that this type of akcent is a typical southwestern feature, one of the lingual markers of the region In question.